2020
DOI: 10.1007/s00484-020-02032-6
|View full text |Cite
|
Sign up to set email alerts
|

Does balneotherapy provide additive effects to physical therapy in patients with subacute supraspinatus tendinopathy? A randomized, controlled, single-blind study

Abstract: This study assessed the additional contribution of balneotherapy on physical therapy in subacute supraspinatus tendinopathy. Ninety patients with subacute supraspinatus tendinopathy were included. They were randomized into two equal groups. In group 1 (n = 45), transcutaneous electrical nerve stimulation (TENS), hot pack, ultrasound treatments, and Codman’s and range of motion (ROM) exercises were performed. In group 2 (n = 45), balneotherapy was added to the treatment program. In both groups, shoulder active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 44 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…Balneotherapy facilities could provide to post-COVID-19 subjects neuromotor rehabilitation with in-water muscle strength and balance exercises and walking recovery (Musumeci et al 2018 ; Masiero et al 2019 ; Morer et al 2020 ) enhancing cardiac (Pagourelias et al 2011 ; Sato et al 2009 ; Yuan et al 2019 ; Persiyanova-Dubrova et al 2019 ; Karaarslan et al 2018 ) or pulmonary performance (Baldi et al 2015 ; Khaltaev et al 2020 ). Moreover, balneotherapy may contribute to the management of comorbidities frequently existing in patients recovered from COVID-19: such as obesity and additional neurological and/or musculoskeletal conditions (Bender et al 2014 ; Fioravanti et al 2015b ; Masiero et al 2018 ; Özkuk and Dilekçi 2019 ; Munteanu et al 2019 ; Özkuk and Uysal 2019 ; Koç et al 2021 ; Eröksüz et al 2020 ; Cantista and Maraver 2020 ; Takinacı et al 2019 ; Dilekçi et al 2019 , 2020 ; Kamioka et al 2020b ; Tenti et al 2020 ; Özkuk and Ateş 2020 ; Yücesoy et al 2021 ; Karaarslan et al 2021 ). Finally, balneotherapy facilities could offer post-COVID-19 subjects with psychologically supportive interventions, reducing psychological consequences such as stress, anxiety, and depression (Stier-Jarmer et al 2017 ; Yang et al 2018 ; Özkuk et al 2018 ; Naumann et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Balneotherapy facilities could provide to post-COVID-19 subjects neuromotor rehabilitation with in-water muscle strength and balance exercises and walking recovery (Musumeci et al 2018 ; Masiero et al 2019 ; Morer et al 2020 ) enhancing cardiac (Pagourelias et al 2011 ; Sato et al 2009 ; Yuan et al 2019 ; Persiyanova-Dubrova et al 2019 ; Karaarslan et al 2018 ) or pulmonary performance (Baldi et al 2015 ; Khaltaev et al 2020 ). Moreover, balneotherapy may contribute to the management of comorbidities frequently existing in patients recovered from COVID-19: such as obesity and additional neurological and/or musculoskeletal conditions (Bender et al 2014 ; Fioravanti et al 2015b ; Masiero et al 2018 ; Özkuk and Dilekçi 2019 ; Munteanu et al 2019 ; Özkuk and Uysal 2019 ; Koç et al 2021 ; Eröksüz et al 2020 ; Cantista and Maraver 2020 ; Takinacı et al 2019 ; Dilekçi et al 2019 , 2020 ; Kamioka et al 2020b ; Tenti et al 2020 ; Özkuk and Ateş 2020 ; Yücesoy et al 2021 ; Karaarslan et al 2021 ). Finally, balneotherapy facilities could offer post-COVID-19 subjects with psychologically supportive interventions, reducing psychological consequences such as stress, anxiety, and depression (Stier-Jarmer et al 2017 ; Yang et al 2018 ; Özkuk et al 2018 ; Naumann et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only five studies showed a sample with more than one hundred participants ( Sekine et al, 2006 ; Yang et al, 2018 ; Rapolienė et al, 2020 ; Stier-Jarmer et al, 2020 ; Maindet et al, 2021 ). The studies included in the review were on healthy or sub-healthy subjects ( Sekine et al, 2006 ; Kamioka et al, 2009 ; Blasche et al, 2010 ; Latorre-Román et al, 2015 ; Stier-Jarmer et al, 2020 ) and patients affected by different pathologies (mainly chronic pathologies or syndromes, i.e., fibromyalgia ( Buskila et al, 2001 ; Neumann et al, 2001 ; Altan et al, 2004 ; Dönmez et al, 2005 ; Maindet et al, 2021 ), ankylosing spondylitis ( Altan et al, 2006 ; Bestaş et al, 2022 ), osteoarthritis ( Yurtkuran et al, 2006 ; Evcik et al, 2007 ), musculoskeletal pain ( Rapolienė et al, 2020 ; Özkuk and Ateş, 2020 ), morbid obesity ( Koçak et al, 2020 ), mental disorders ( Koike et al, 2013 ; Naumann et al, 2020 ) and subacute supraspinatus tendinopathy ( Koç et al, 2021 )).…”
Section: Resultsmentioning
confidence: 99%
“…Except for the study by Sekine and colleagues (2006), all the studies set up a balneotherapy intervention protocol, with more than half of the studies (sixteen) showing both an intervention and control (or with other therapies excluding balneotherapy) group ( Buskila et al, 2001 ; Neumann et al, 2001 ; Altan et al, 2004 , 2006 ; Dönmez et al, 2005 ; Yurtkuran et al, 2006 ; Kamioka et al, 2009 ; Yang et al, 2018 ; Naumann et al, 2020 ; Rapolienė et al, 2020 ; Stier-Jarmer et al, 2020 ; Özkuk and Ateş, 2020 ; Koç et al, 2021 ; Maindet et al, 2021 ; Bestaş et al, 2022 ), whereas the remaining studies did not randomize the study sample ( Evcik et al, 2007 ; Blasche et al, 2010 ; Koike et al, 2013 ; Latorre-Román et al, 2015 ; Koçak et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations